Site audit and reporting of telecommunication tower / Aiman Nurhakim Ahmad Khanzir - Ahmad Khanzir, Aiman Nurhakim (2021)
Telecommunication tower is very important thing to elaborate. This is because telecommunication tower is one of the most importance structural in our daily life. Moreover, currently there is limited research conducted on telecommunication tower in communication. Furthermore, this report was conducted for the Touch Matrix Sdn. Bhd (TMX). Moreover, the aim of this report is to site audit for Touch Matrix and to determine the proper rates to be imposed on telecommunication tower renters. Besides, this study is carried out by using two suitable method, including observation and refer the masterlist given by Touch Matrix. To summarize, telecommunication tower is most important in telecommunication system. Also, can determine the kind of structure it is and learn more about how the telecommunication tower function.